Cell Type‐Specific Modulation of Acute Itch Processing in the Anterior Cingulate Cortex - Jiaqi Li; Yang Bai; Junye Ge; Yiwen Zhang; Qiuying Zhao; Dangchao Li; Baolin Guo; Shasha Gao; Yuanyuan Zhu; Guohong Cai; Xiangdong Wan; Jing Huang; et al. (Advanced Science, 2024)
Abstract Despite remarkable progress in understanding the fundamental bases of itching, its cortical mechanisms remain poorly understood. Herein, the causal contributions of defined anterior cingulate cortex (ACC) neuronal populations to acute itch modulation in mice are established. Using cell type‐specific manipulations, the opposing functions of ACC glutamatergic and GABAergic neurons in regulating acute itching are demonstrated. Photometry studies indicated that ACC glutamatergic neurons are activated during scratching induced by both histamine and chloroquine, whereas the activation pattern of GABAergic neurons is complicated by GABAergic subpopulations and acute itch modalities. By combining cell type‐ and projection‐specific techniques, a thalamocortical circuit is further identified from the mediodorsal thalamus driving the itch‐scratching cycle related to histaminergic and non‐histaminergic itching, which is contingent on the activation of postsynaptic parvalbumin‐expressing neurons in the ACC. These findings reveal a cellular and circuit signature of ACC neurons orchestrating behavioral responses to itching and may provide insights into therapies for itch‐related diseases.